Neurological Crisis Following Intravenous Ozone Therapy; a Case Report - Chloe Y Y Wong; Komal Saxena; John Meneer; Koshy George; Gerben Keijzers (Archives of Academic Emergency Medicine, 2025)
Ozone therapy, often marketed as an immune-boosting alternative treatment, lacks robust evidence of efficacy and poses significant safety risks. Despite claims of therapeutic benefits, Regulatory agencies, such as the U.S. Food and Drug Administration (FDA), warn against its use due to its toxic properties and lack of proven benefits at tolerable exposure levels. This case report highlights severe neurological complications, including ischemic infarcts and persistent cognitive deficits, following intravenous ozone (O3) therapy in a previously healthy patient. A 36-year-old woman presented to the emergency department with chest pain, syncope, and generalized seizure shortly after receiving intravenous ozone therapy. Diagnostic imaging revealed multiple ischemic infarcts in the thalamus and cerebellum, consistent with an embolic event. The patient required intensive care unit (ICU) admission, and despite improved neurological function experienced lasting cognitive impairments necessitating long-term rehabilitation.